Impact of Workplace Romance on Organizational Settings and Policies : Review Research - Sidhu, Amrita; Bhalla, Pretty; Nazneen, Afroze (Prabandhan: Indian Journal of Management, 2020)
Workplace romance has become a very common phenomenon in each and every type of industry. The goal of this study was to analyze the changing trend of workplace romance in the organizations in addition to exploring new factors leading to its formation and impact on organizational settings. This research also discussed about the various policies required in this context. A review research was conducted by taking into consideration some of the relevant studies on workplace romance (WPR). The findings of this study provided various new factors like attachment styles, psychological well - being, aestheticization of work, employees’ attitude about workplace romance, prior engagement in workplace romance, and conscientiousness, which provided a boost to WPR in organizations as compared to traditional WPR parameters like proximity, attitudinal similarity, romantic motives, and organizational climate. Looking at the impact, the study showed both positive and negative impact of workplace romance on the organizational settings in terms of employee performance, co-worker’s attitude, organizational commitment, and organizational environment. As far as policies are concerned, a list of suggestions is provided for framing a correct WPR policy to manage such relationships in an organization.